Hubungan Dukungan Keluarga dengan Kualitas Hidup Pasien Diabetes Mellitus Tipe 2 di Puskesmas Helvetia Medan - Nuryatno Nuryatno (Journal of Health Science and Physiotherapy, 2019)
The number of Diabetes Mellitus (DM) patients in Indonesia was 5,6 million people in 2001 and if increased to 9 million people in 2014. The data from Medan Health Service revealed that the number of DM patients was 27,075 people in 2013 and it was 3,607 people only from January to February 2014. The objective of the research was to analyze the correlation of family support, viewed from the dimensions of empathy/emotion, recognition, instrumental, and information with the life quality of DM type 2 patients at Helvetia Health Center, Medan. The research was a survey with a cross-sectional design. The population was 43 DM Type 2 patients, and all of them were used as the samples. The data were gathered by using questionnaires and analyzed by using univariate, analysis, bivariate analysis with chi-square test at the significance level of 95%. The result of the research showed the there was the correlation of family support with the dimensions of empathy/emotion, recognition, instrumental, and information with the life quality of DM type 2 patients. It is recommended that Helvetia Health Center, Medan, empower health care providers in providing health promotion like education and counseling for DM Type 2 patients and their familiar. The patient familiar should pay serious attention and give information about DM in order that DM Type 2 patients can improve their life quality and will be able to accept their own condition patiently in medication and their own life